Increase in maximal cycling power with acute dietary nitrate supplementation - Rimer, E. G.; Peterson, L. R.; Coggan, A. R.; Martin, J. C. (International Journal of Sports Physiology and Performance, 2016)
Muscle-shortening velocity and hence power have been shown to increase in the presence of nitric oxide (NO). NO availability increases after consuming nitrate (NO3-). Ingestion of NO3-rich beetroot juice (BRJ) has increased muscle power in untrained adults.